AKOMODASI BUDAYA SEBAGAI MODEL KEBERTERIMAAN KESENIAN BARONGSAI - Ansari, Isa (Acintya, 2018)
The main objective of this research was to create a model of social integration in the performance of Barongsai Dance and to build understanding of multicultural awareness based on traditional arts. The target of this study was the formulation of a social integration model in the performance of Barongsai Dance. To achieve this goal, researchers used descriptive analytical methods. The data were obtained by conducting interviews, observation, documentation.Â  The results of this researchhave formulated an accommodation model through an adaptation process. Adaptation that is done is in the attitude adaptation which is by strengthening the emotive and cognitive elements. The second is functional adaptation by adapting to ritual functions, entertainment functions, and sports and competition functions.Â Keywords: Integration Model, BarongsaiDance, Acceptance